Analysis of paddlesport commitment and multiple outcomes: A serious leisure perspective - Lee, KoFan (Cogent social sciences, 2017)
Paddlesports as outdoor recreation (OR) have become popular options for leisure time consumption and as a means to obtain well-being. The concept of serious leisure (SL) was used to measure and explain the associations between committed leisure experiences and multiple outcomes in a sample (n = 171) of paddlesport enthusiasts. CFA fit indices revealed that all models demonstrated acceptable fit, which justified the creations of composite-level indicators. A path analysis was then conducted to assess the relationship between the six factors of a SL experience and multiple outcomes: personal, social and financial. Path analysis revealed that SL experiences partially explained the variances of personal outcomes (46%), social outcomes (53%) and financial return (21%). The path model showed that personal and social outcomes were positively associated with most SL factors but financial return was not significantly predicted by any SL factor. SL factor career contingency was negatively associated with personal outcomes at the p < .01 level, a potential indication of the costs of their commitment to paddling. The results of this study indicated factors enhanced or hindered personal and social developments gained from SL participation. This suggests that outdoor recreation practitioners may develop customized strategies to sustain clients’ healthy engagements in the pursuit.